Presence of the GFI1-36N single nucleotide polymorphism enhances the response of MLL-AF9 leukemic cells to CDK4/6 inhibition - Vorwerk, Jan; Sun, Kaiyan; Frank, Daria; Neumann, Felix; Hüve, Jana; Budde, Paulina Marie; Liu, Longlong; Xie, Xiaoqing; Patnana, Pradeep Kumar; Ahmed, Helal Mohammed Mohammed; Opalka, Bertram; Lenz, Georg; et al. (Frontiers in Oncology, 2022)
The zinc finger protein Growth Factor Independence 1 (GFI1) acts as a transcriptional repressor regulating differentiation of myeloid and lymphoid cells. A single nucleotide polymorphism of GFI1, GFI1-36N, has a prevalence of 7% in healthy Caucasians and 15% in acute myeloid leukemia (AML) patients, hence most probably predisposing to AML. One reason for this is that GFI1-36N differs from the wildtype form GFI1-36S regarding its ability to induce epigenetic changes resulting in a derepression of oncogenes. Using proteomics, immunofluorescence, and immunoblotting we have now gained evidence that murine GFI1-36N leukemic cells exhibit a higher protein level of the pro-proliferative protein arginine N-methyltransferase 5 (PRMT5) as well as increased levels of the cell cycle propagating cyclin-dependent kinases 4 (CDK4) and 6 (CDK6) leading to a faster proliferation of GFI1-36N leukemic cells in vitro. As a therapeutic approach, we subsequently treated leukemic GFI1-36S and GFI1-36N cells with the CDK4/6 inhibitor palbociclib and observed that GFI1-36N leukemic cells were more susceptible to this treatment. The findings suggest that presence of the GFI1-36N variant increases proliferation of leukemic cells and could possibly be a marker for a specific subset of AML patients sensitive to CDK4/6 inhibitors such as palbociclib.